173k views
0 votes
What is 2y/6 = x/6 in y = mx + c form?

User Cong Tran
by
5.6k points

2 Answers

5 votes

All we need to do is deform the given equation,


(2y)/(6)=(x)/(6)

Let's first try to simplify it until x and y terms are independent.


</p><p>(y)/(3)=(x)/(6) \\</p><p>6y=3x \\</p><p>y=(3x)/(6) \\</p><p>\boxed{y=(1)/(2)x+0}</p><p>

Hope this helps.

r3t40

User Kibonge Murphy
by
5.6k points
6 votes

Answer:

see explanation

Explanation:

Given


(2y)/(6) =
(x)/(6)

Multiply both sides by 6 to eliminate the fractions

2y = x ( divide both sides by 2 )

y =
(1)/(2) x ( with c = 0 ) ← in slope- intercept form

User Pab
by
5.9k points